Rock Physical Modeling and Seismic Dispersion Attribute Inversion for the Characterization of a Tight Gas Sandstone Reservoir - Jin, Han; Liu, Cai; Guo, Zhiqi; Zhang, Yiming; Niu, Cong; Wang, Di; Ling, Yun (Frontiers in Earth Science, 2021)
In the rock physical modeling in this study, the complex pore space of tight sands was assumed to be equivalent to the combination of high aspect-ratio pores (stiff pores) and low aspect-ratio microcracks (soft pores). Then, the Chapman theory was used to simulate the elastic properties and inelastic behavior of the dispersion and attenuation caused by the squirt flow of fluids in the complex pore spaces for different gas saturations. The modeling results indicate that as the gas saturation increases, the P-wave velocity decreases at seismic frequencies and dispersion and attenuation occurs at higher frequencies. The velocity dispersion of the tight gas sandstone causes the contrast in the P-wave impedance across the interface between the tight sand and the overlying mudstone vary with frequencies, and thus, the reflection coefficients of the interface are frequency-dependent. The models with different gas saturations in tight sand represent the specific features of frequency-dependent reflection coefficients. The seismic modeling shows that the reflected waveforms have a negative phase when the tight sand is fully saturated with gas and a positive phase when they are fully water saturated. Moreover, these two extreme cases exhibit distinct amplitude versus angle (AVA) features in the seismic reflections. For a scenario between full gas and full water saturation, the reflection coefficients exhibit a more obvious frequency dependence, and polarity reversal occurs in the synthetic AVA gathers. The frequency-dependent AVA inversion using synthetic data revealed that high values of the inverted P-wave dispersion attribute indicate a high gas saturation in tight gas sandstone. There is a significant difference in the inverted dispersion attributes of the two cases of tight sandstone that are fully saturated with gas and with water. Applying the frequency-dependent AVA inversion to the pre-stacked field seismic data revealed that the inverted P-wave dispersion attribute is positively correlated with the gas production from the payzone of the tight gas sandstone. The methods used for the rock physics modeling and the frequency-dependent AVA inversion conducted in this study have good potentials for the evaluation of the degree of gas saturation in tight gas sandstone reservoirs.